Experience: the most critical factor in choosing after-hours medical care. Issue 6 (29th April 2010) - Philips, H; Mahr, D; Remmen, R; Weverbergh, M; De Graeve, D; Van Royen, P
Abstract : Introduction: In many countries, a reassessment of after-hours primary care has become necessary. In particular, centralised general practitioner deputizing services (GPDS) have emerged. In this study, consumers' preferences for after-hours medical care were obtained and the use of the new GPDS was predicted. Method: On the basis of the Theory of Reasoned Action, a survey was developed that was used at the Free Newborn and Child health care services in Antwerp. Consumers were asked about their knowledge, experience and perceptions concerning the performance of different medical services. Results: 350 questionnaires were used for analysis. 98.6% of the respondents knew about the existence of the emergency department, whereas the GPDS was known by 81.7% of the respondents. The main reasons for preferring emergency department over the other services were an easy access, good explanation by the doctor and a late due time of the payment. Respondents preferred the GPDS mainly because of an expected shorter waiting time. Experience had a strong positive influence on choosing a particular after-hours medical service. Conclusion: In our study, the consumers' preferences concerning after-hours medical care were assessed. The following items are crucial for choosing after-hours care: experience with the services, easy access to the service, explanation by the doctor about the illness and the treatment and waiting time.